Menstrual Poverty: A Public Health Crisis and the Vital Role of School Healthcare Providers in Iran - Zahra Saboohi; Ghavami maryam (International Journal of Community Based Nursing and Midwifery, 2025)
The World Bank predicts that by 2030, 574 million people will live in extreme poverty, limiting access to basic needs such as food, water, and shelter.1 One overlooked aspect of poverty is “menstrual poverty,” which refers to the lack of access to menstrual hygiene products, education, and facilities due to financial and social barriers. It affects millions of women and girls who menstruate and with significant physical, emotional, and social consequences, including absenteeism from school and work, as well as mental health problems.2